2019
DOI: 10.1038/s41419-019-1846-0
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of eukaryotic translation initiation factor 3b inhibited proliferation and metastasis of gastric cancer

Abstract: Eukaryotic translation initiation factor 3 (eIF3) plays an important role in the regulation of mRNA translation, cell growth and cancer development. eIF3b is the main scaffolding subunit in the eIF3 complex and has been demonstrated to contribute to the development of several cancers. First, our study found that the downregulation of eIF3b could inhibit the proliferation and metastasis of gastric cancer cells by regulating the expression of cancer-related genes. In addition, the expression of eIF3b correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…All of these results indicate that EIF3B has an important role in cancer-associated processes. A previous study suggested that EIF3B is involved in the proliferation and metastasis of gastric cancer (39). In addition, the present study further determined that EIF3B is associated with the histologic grade and survival status of patients with liver cancer.…”
Section: Discussionsupporting
confidence: 72%
“…All of these results indicate that EIF3B has an important role in cancer-associated processes. A previous study suggested that EIF3B is involved in the proliferation and metastasis of gastric cancer (39). In addition, the present study further determined that EIF3B is associated with the histologic grade and survival status of patients with liver cancer.…”
Section: Discussionsupporting
confidence: 72%
“…For example, reports revealed DDX21 could affect the proliferation of GC cells by up‐regulating levels of cyclin D1 and CDK2 . Likewise, the suppression of EIF3B inhibits the proliferation and metastasis of GC by effectively modulating the expression of cancer‐related genes . Likewise, we also found 15 co‐expression relationships in RBP interactions such as CPSF3 , DDX18 , DKC1 , and FUS (Table ).…”
Section: Resultssupporting
confidence: 58%
“…Protein extraction and western blot were performed as previously described [28]. Antibodies were as follows: NFIB (Abcam, ab186738, Cambridge, UK, 1:1000 dilution) and GAPDH (CST, #5174, MA, USA, 1:3000 dilution).…”
Section: Protein Extraction and Western Blotmentioning
confidence: 99%